Dual-plating aqueous Zn-iodine batteries enabled by halogen-complexation chemistry for large-scale energy storage - Li, Hong (2025)
Aqueous Zn-I2 batteries are promising candidates for grid-scale energy storage due to their low cost, high voltage output and high safety. However, Ah-level Zn-I2 batteries have been rarely realized due to formidable issues including polyiodide shuttling and zinc dendrites. Here, we develop 10 Ah dual-plating Zn-I₂ batteries (DPZIB) by employing ZnIxG4(tetraglyme) complex chemistry, in which zinc and iodine are iteratively dissolved and deposited in the aqueous electrolyte. The battery contains no membrane or high-cost electrolytes. The G4 strengthens the Zn-I bond by acting as an electron donor, and meanwhile, it enhances the reductivity of electrolyte by its complexation with Zn2+. Such halogen-complexation chemistry endows static DPZIB with shuttle-free property, negligible self-discharge, and minimal zinc dendrites. The battery delivers a capacity of 301.5 mAh over 1800 h at 5 mA cm-2, a low capacity decay (0.028% drop per cycle for 800 cycles at 25 mA cm-2), and a scalable capacity of up to 10.8 Ah. As a proof of concept, we demonstrate an integrated system encompassing a membrane-free Zn-I2 flow battery to store solar electricity at daytime and power electronics at nights.